A predicting model of PaTs' performance in off-design operating conditions. (February 2019) - Rossi, Mosè; Nigro, Alessandra; Renzi, Massimiliano
Abstract: The aim of this work is to propose a predicting model for evaluating Pump-as-Turbines' (PaTs) performance in off-design operating conditions. The predicting model has been derived from an elaboration of experimental test data available in literature on a set of several pumps operating in reverse mode. The performance prediction capability of the model has been compared with the results of the Computational Fluid Dynamics (CFD) analysis of a centrifugal pump running in turbine mode for several operating conditions. The comparison of the performance predicted by the model and the ones obtained with the numerical analysis has allowed to evaluate the effectiveness of the proposed model, highlighting its pros and cons and possible improvements. In general, it is possible to conclude that the proposed model is able to correctly assess the work and the efficiency of the studied PaT within errors in the range of few percentage points, especially for operating conditions not so far from the designed one.